Freshwater Amphipod Species of Western Anatolia, Marmara and Turkish Thrace Regions - Mehmet İpek; Murat Ozbek (Aquatic Sciences and Engineering, 2022)
To determine the Amphipoda (Crustacea) fauna of the inland waters of Western Anatolia, Marmara and the Turkish Thrace Region, field studies were conducted between May 2014 and March 2019. Sevenfieldstudieswereconducted.Samplingswereconductedat291localitiesandamphipodspecimens were found at 127 of them. As a result, 11 amphipod species (Echinogammarus stockiG.Karaman,1970,Gammarusaequicauda(G.Karaman,1970),GammarusanatoliensisSchellen-berg,1937,GammarusarduusG.Karaman,1975,GammarusbalcanicusSchäferna,1923,Gam-marusdorsosetosusMateus amp;Mateus,1990,GammarusgonensisÖzbek,2016,Gammarus komareki Schäferna, 1923, Gammarus lacustris G.O. Sars, 1863, Gammarus pulex pulex (Linnaeus, 1758), Gammarus uludagi G.S. Karaman, 1975) were determined. The new records can be listed as: E. stocki for Ekinanbarı, G. anatoliensis for Uşak, G. arduus for Bolu and Düzce, G. balcanicus for Kocaeli and Sakarya, G. dorsosetosus for Bolu, G. gonensis for Istanbul and Manisa, G. komarekifor Düzce and Kocaeli, G. lacustris for Istanbul, G. pulex pulex for Bolu, Kırklareli, Kocaeli, Sakarya and Uşak, and G. uludagi for Aydın, Bilecik, Sakarya and Yalova provinces. The observed morpho-logical features and the detailed drawings of the determined taxa are presented. Additionally, a map showing the distribution of the obtained species is also given.